Representasi Keris Dan Pembentukan Kebijakan Baru Dalam Narasi Rebranding Pariwisata Sumenep - Putra, Deny Fardiansyah; Anugerah, Ahmed David; Kurli, Anis (Jurnal Desain Komunikasi Visual Asia, 2025)
Rebranding keris as a tourism icon of Sumenep district is a new narrative that has been built by the people of Sumenep based on their assessment of the life of the people who can not be separated from the heirloom. The narrative of rebranding the keris as a tourism icon has relevance to the purpose of efforts to create a strong image impression on tourists, this is because the keris has become part of the archipelago community and even known to the world community. Based on this reality, this study aims to determine how the representation of the value of the keris in the discourse of tourism rebranding, how the visualization of the value of the keris in supporting the discourse of tourism rebranding, how the local government policy in an effort to strengthen the rebranding of the keris as a new icon of tourism in Sumenep. The method used is qualitative with semi-structured interview data collection techniques. The results of this study indicate the keris as a representation of the way of life of the people of Sumenep inherent in daily life so that the icon of the keris as a new branding can create a strong and unique image for tourist destinations, while also strengthening awareness of local cultural values. In addition, rebranding the keris as a tourism icon of Sumenep through the creation of a logo can build a self-image as a tourism centre that is different from destinations in general. Finally, the form of government support in realizing the discourse of keris rebranding as a new tourism icon can be realized through several concrete and strategic forms of support such as the creation of local government regulations.